The Correlation Between Students’ Motivation and Their Writing Ability During Online Learning in 7th Grade at MTsN 2 Payakumbuh - Fatmawati Fatmawati; Loli Safitri; Reflinda Reflinda; Syahrul Syahrul (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find the correlation between students' motivation and writing ability during online learning. This research was conducted at MTsN 2 Payakumbuh because it cannot be denied that there are still students who face problems in writing, including students who are not interested and feel bored while studying, some students feel unmotivated to complete assignments, and students who have difficulty writing in English. The research method used is quantitative with a correlational design. The data were collected by using a questionnaire consisting of 30 statements to determine the level of student motivation, and students' writing scores during online learning to determine the level of students' writing ability. Researcher used 35 students from a population of 140 students with purposive sampling technique. To analyze the data, the researcher used the Spearman’s Rank. The results showed there is no significant correlation between students' motivation and their writing ability during online leaerning in 7th grade at MTsN 2 Payakumbuh” in this research.The researcher found the correlation coefficient between student motivation and writing ability in 7th grade MTsN 2 Payakumbuh was 0,102. Meanwhile t-table on df = 33 and = 0,05 was 0.344. It means, the rs was smaller than ttable and Ha is rejected. The magnitude lies between 0,00 – 0,199. Thus, there is a positive correlation between student motivation and writing ability during online learning in 7th grade MTSN 2 Payakumbuh.